The Implementation of Islamic Sharia in the Enforcement of Qanun Jinayat in Aceh: A Legal Analysis and Social Impact - Juliandika, Adam; Fazzan, Fazzan (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The Qanun Jinayat is a regional regulation in Aceh that implements Islamic Sharia within the local criminal justice system. This article analyzes the application of the Qanun Jinayat, examining the legal aspects and social impacts it creates within the Acehnese community. Using normative juridical research methods and literature analysis, this study aims to illustrate the effectiveness of the Qanun Jinayat and the challenges encountered in its implementation, particularly regarding human rights issues and social acceptance. The findings indicate that the application of the Qanun Jinayat plays a significant role in strengthening Islamic identity in Aceh. However, challenges arise, requiring further oversight and harmonization with national legal principles and human rights values. Abstract: Qanun Jinayat merupakan peraturan daerah di Aceh yang mengimplementasikan syariat Islam dalam sistem hukum pidana lokal. Artikel ini menganalisis penerapan Qanun Jinayat dengan meninjau aspek hukum dan dampak sosial yang ditimbulkan di masyarakat Aceh. Penelitian ini menggunakan metode penelitian normatif yuridis dan analisis literatur untuk menggambarkan efektivitas Qanun Jinayat serta tantangan dalam implementasinya, terutama terkait isu hak asasi manusia dan penerimaan sosial. Hasil penelitian menunjukkan bahwa penerapan Qanun Jinayat berperan penting dalam memperkuat identitas Islam di Aceh, meskipun terdapat tantangan yang memerlukan pengawasan dan harmonisasi lebih lanjut dengan prinsip hukum nasional serta nilai-nilai HAM.